2006
DOI: 10.1097/01.aids.0000198086.39831.4a
|View full text |Cite
|
Sign up to set email alerts
|

Association of genital shedding of herpes simplex virus type 2 and HIV-1 among sex workers in rural Zimbabwe

Abstract: Rate and quantity of HIV-1 genital shedding do not appear to be altered by presence of HSV-2 genital shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Such association may be due to the fact that the viruses are both sexually transmitted and must share risk factors. It may also be due to the fact that one virus increases the risk of transmission of the other [2,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such association may be due to the fact that the viruses are both sexually transmitted and must share risk factors. It may also be due to the fact that one virus increases the risk of transmission of the other [2,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Genital herpes is most frequently caused by herpes simplex virus type 2 (HSV-2). Findings of clinical, biological, and epidemiological studies support the hypothesis that HSV-2 increases the risk of HIV-1 acquisition 2-4-fold [2][3][4][5][6][7][8][9][10] and increases the risk of HIV-1 transmission [2,[11][12][13][14]. A recent meta-analysis found that, in fixed-effects analyses, the presence of HSV-2 shedding significantly affected HIV shedding in genital tract specimens (OR, 1.5; 95% CI, 1.0 -2.1) [15].…”
mentioning
confidence: 92%
“…Cross-sectional studies of women in Mombasa [4] and Bangui [5] have shown positive correlations between the quantities of genital HIV-1 RNA and genital HSV-2 DNA in persons coinfected with these viruses, whereas a Zimbabwean study did not find any association [6]. The high variability of HIV-1 and HSV-2 genital shedding, both within and between individuals, has been widely reported in large studies from the United States that involved daily sampling [7][8][9], highlighting the need for a longitudinal design with multiple measurement points in order to best describe HIV-1 and HSV-2 genital shedding and identify their correlates.…”
mentioning
confidence: 90%
“…Moreover, it has been evidenced that HSV-2 significantly increases the dissemination of HIV in the genitalia of those co-infected with these viruses [113]. It is important to note that the relationship between HIV and HSV-2 is reciprocal, as infection with HIV also significantly increases the probability of acquiring HSV-2, and that reactivation with HSV-2 is more frequent in HIVpositive patients [114][115][116]. Noteworthy, the relationship between HSV-2 and HIV is synergic and goes beyond risk factors associated with the acquisition of these viruses.…”
Section: Relationship Between Hsv-2 and Hivmentioning
confidence: 99%